Biomechanical Effects of 3D-Printed Bioceramic Scaffolds With Porous Gradient Structures on the Regeneration of Alveolar Bone Defect: A Comprehensive Study - Yang, Zhuohui; Wang, Chunjuan; Gao, Hui; Jia, Lurong; Zeng, Huan; Zheng, Liwen; Wang, Chao; Zhang, Hongmei; Wang, Lizhen; Song, Jinlin; Fan, Yubo (Frontiers in Bioengineering and Biotechnology, 2022)
In the repair of alveolar bone defect, the microstructure of bone graft scaffolds is pivotal for their biological and biomechanical properties. However, it is currently controversial whether gradient structures perform better in biology and biomechanics than homogeneous structures when considering microstructural design. In this research, bioactive ceramic scaffolds with different porous gradient structures were designed and fabricated by 3D printing technology. Compression test, finite element analysis (FEA) revealed statistically significant differences in the biomechanical properties of three types of scaffolds. The mechanical properties of scaffolds approached the natural cancellous bone, and scaffolds with pore size decreased from the center to the perimeter (GII) had superior mechanical properties among the three groups. While in the simulation of Computational Fluid Dynamics (CFD), scaffolds with pore size increased from the center to the perimeter (GI) possessed the best permeability and largest flow velocity. Scaffolds were cultured in vitro with rBMSC or implanted in vivo for 4 or 8 weeks. Porous ceramics showed excellent biocompatibility. Results of in vivo were analysed by using micro-CT, concentric rings and VG staining. The GI was superior to the other groups with respect to osteogenicity. The Un (uniformed pore size) was slightly inferior to the GⅡ. The concentric rings analysis demonstrated that the new bone in the GI was distributed in the periphery of defect area, wheras the GII was distributed in the center region. This study offers basic strategies and concepts for future design and development of scaffolds for the clinical restoration of alveolar bone defect.